Pelanggaran Hak Cipta Karya Fotografi Di Media Daring Menurut Hak Kekayaan Intelektual - Karina Putri; Nahrowi Nahrowi (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2020)
This study aims to examine the legal protection of copyright creators of photographic works whose moral and economic rights are violated on the internet according to Law Number 28 of 2014 concerning Copyright. This research method uses a normative juridical research approach, namely research that refers to the legal norms that exist in statutory regulations, literature, expert opinion and papers. The results in this study indicate that photographic copyright infringement is still rife, referring to one of Aryono's cases, where photos on his personal Instagram were taken by online media for commercial purposes. In this case there was a violation of moral rights and economic rights. In the Copyright Law, it is explained in article 5 that moral rights are attached to the creator to maintain the creator's right which is valid for life and if used for commercial purposes, it is explained in Article 9 that the creator has economic rights, that is, everyone is required to obtain the author's permission to carry out commercial use of this protection. valid for 50 years.Keywords: Photographic Copyright, Copyright Infringement